Logic and Computation - Diaconescu, Răzvan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains five articles accepted and published in the Special Issue "Logic and Computation 2023" of the MDPI "Mathematics" journal, covering several topics on computing science based on some form of logic. These topics include the model theory for formal logic-based formal specification and programming, logic mining and logic for games. It is hoped that the reprint will be interesting and useful for those working in the area of applying logic to computing.